Estimating downwind turbulence intensity using wind and wave measurements during hurricanes. (July 2019) - Shen, H.; He, Y.; Hsu, S.A.
Highlights: Under high wind conditions, relationship between overwater downwind turbulence intensity (TI) and wind speed is obtained from measurements. Based on the proposed TI parameterization, overwater friction velocity ( U * ) can also be obtained. The formula is verified by state-of-the-art results from the eddy-covariance, the wind gust and the wind-current interaction methods. In addition, the proposed formula is shown to be valid up to U 10 = 56 m s −1 as compared to recent analysis on Super Typhoon Megi (2010). Abstract: Analyses of simultaneous measurements of wind speed at 10 m, U 10, significant wave height, H s and peak wave period, T p from 3 National Data Buoy Center (NDBC) buoys during the passage of 6 hurricanes over the wind seas when U 10 ≥ 9 m s −1 indicate that overwater downwind turbulence intensity (TI) can be formulized as T I = - 6.06 × 10 - 5 U 10 2 + 4.93 × 10 - 3 U 10 + 3.95 × 10 - 2, here U 10 is the wind speed at 10 m height over sea surface. It is found that TI = 0.08 when U 10 = 9 m s −1, and it peaks up to approximately 0.14 when U 10 ≈ 40 m s −1 . Thereafter, TI saturates as U 10 continuously increases. From this TI formulation, overwater friction velocity ( U * ) is inferred as U * = 0.4 0 U 10 ( - 6.06 × 10 - 5 U 10 2 + 4.93 × 10 - 3 U 10 + 3.95 × 10 - 2 ) . This friction velocity parameterization is further verified by 3 independent methods: the direct eddy covariance, the wind gust and the wind-current interaction. It shows that this proposed U * formula is valid up to U 10 = 56 m s −1 during Super Typhoon Megi (2010) as validated by measurements based on the wind-current interaction method.